Impact of Taxation on Economic Growth: Case study of sub-Saharan African Countries - Kandoje, Natasha (School of Economics, 2023)
This paper investigates the effects of taxes on economic growth by using a dynamic panel regression analysis on 35 countries in sub–Saharan Africa (SSA)1 region over the 2009–2020 period. The analysis is executed using a dynamic panel regression model, System Generalized Methods of Moments (GMM). The findings of this paper suggest that different tax types have different effects on economic growth. Income taxes and corporate taxes have a statistically significant negative impact on economic growth. In contrast, value-added tax (VAT) exhibits a statistically significant positive relationship with economic growth. Therefore, according to these findings, policymakers in the SSA region should consider lowering income and corporate taxes while raising VAT because these policy combinations may increase long-term economic growth.